Are stock market returns related to the weather effects factors? empirical evidence from Malaysia / Suzaida Bakar and Noraina Mazuin Sapuan - Bakar, Suzaida; Sapuan, Noraina Mazuin (2012)
In this study, we attempted to determine whether a relationship exists between stock returns and the weather variables using the econometric technique of the regression with the GJR - GARCH model. The major weather factors have been studied include temperature, rainfall and humidity in Malaysian stock market by using monthly data for the period of January 1983 until December 2008. From our findings, we find out that temperature has strong effects on stock market returns and stock return tend to be lower when the weather is extremely hot. The high or low temperature as suggested by psychologist would make people impatient and upset, thus it would affect investors behavior when they make decisions in view of the bounded rationality.We hope that our empirical findings further support the previous arguments that advocate the inclusion of economically neutral behavioral variables in asset pricing models. The results also might have significant implications for individual investors and financial institutions planning to invest in the Malaysia stock market.